Peran Lingkungan Pendidikan Islam Dalam Pembentukan Karakter Peserta Didik - Nurzamsinar; Sudirman; Daimah; Wahid, Abd. (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2025)
Islamic education is oriented towards the formation of a perfect human being, a person who is balanced in spiritual, intellectual, and moral aspects. In the process of achieving this goal, the environment plays a very strategic role. The Islamic educational environment is not only limited to formal institutions, but also includes the family environment, society, and even the natural environment as a learning medium. This study aims to identify the role and contribution of each type of educational environment in supporting the formation of student character based on Islamic values. This study uses a qualitative approach with a literature study method, reviewing various classical and contemporary literature related to Islamic education and environmental theory. The results of the study indicate that the family environment serves as the initial foundation in instilling faith and morals, the school environment or Islamic boarding school as a formal education system plays a role in intellectual development and spiritual skills, the community environment functions as a socio-religious reinforcement, while the natural environment encourages students to engage in contemplation and tadabbur as part of strengthening spirituality. The synergy between these four environments is crucial to forming students who are not only academically intelligent, but also faithful, pious, and have noble character. Therefore, the development of an ideal Islamic education system must consider holistic integration between environments. Keyword: Islamic Education, Educational Environment, Character, Students.